Persecutory policies against Roma in Nazi Germany - Andrej Pupik (Journal of Political Science: Bulletin of Yerevan University)
The article provides an analysis of the persecution measures against the Roma in Nazi Germany, identifying what measures were taken and, in particular, what tragic consequences they led to on a practical level. The article comparatively analyzes various aspects of the persecution of Roma in Germany, and indeed throughout Europe, preceding the totalitarian seizure of power by the Nazis in 1933 and the emergence of Nazi Germany. The main focus is on identifying the stages of the persecution policy in Nazi Germany against Roma, as well as the chronology of the adoption of the persecution policy against Roma in Nazi Germany in 1933-1945. As a result, a turning point in the anti-Roma policy is identified and characterized, which included both the freezing of Roma mobility and the resettlement of Roma, as well as their deportation to Auschwitz-Birkenau.